2017
DOI: 10.1007/s10068-017-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new oligosaccharide converted from cellobiose by novel strain of Bacillus subtilis

Abstract: Six bacterial strains isolated from various Korean fermented foods were cultured in cellobiose-containing medium to investigate their potential for producing new kind of oligosaccharides. After bacterial culture in a liquid medium, each culture medium was concentrated and analyzed. TLC analysis revealed that only one strain ( SS-76) produced new spot on the TLC plate, indicating that it could converts cellobiose into a new oligosaccharide. Following purification of the culture supernatant of SS-76, the fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…They do not, however, explain how individual carbon sources behave in higher-order combinations. For example, though the community grown on D-cellobiose displayed high taxonomic diversity (possibly sustained via cross-feeding of L-lactate from B. subtilis 39,40 ), all organisms were overtaken by P. aeruginosa when D-cellobiose was combined with glycerol ( Figure 3a). We therefore generated a simple linear model to determine whether any particular carbon sources were more universally associated with higher taxonomic diversity.…”
Section: Com13 (Supplementarymentioning
confidence: 99%
See 1 more Smart Citation
“…They do not, however, explain how individual carbon sources behave in higher-order combinations. For example, though the community grown on D-cellobiose displayed high taxonomic diversity (possibly sustained via cross-feeding of L-lactate from B. subtilis 39,40 ), all organisms were overtaken by P. aeruginosa when D-cellobiose was combined with glycerol ( Figure 3a). We therefore generated a simple linear model to determine whether any particular carbon sources were more universally associated with higher taxonomic diversity.…”
Section: Com13 (Supplementarymentioning
confidence: 99%
“…Despite our observation that an organism's performance in monoculture is rarely correlated with its persistence in a community ( Supplementary Figure 19), the ability of B. subtilis to efficiently metabolize D-cellobiose ( Supplementary Figure 2a) may provide clues to its high abundance in this case. Specifically, B. subtilis has been documented to convert cellobiose to L-lactate 47,48 . Our initial phenotypic assays showed that P. aeruginosa and S. oneidensis, the next most prevalent organisms in this community, can utilize L-lactate, indicating the possibility of cross-feeding.…”
Section: Mapping Nutrient Identity To Community Diversitymentioning
confidence: 99%
“…lactis CCK940 exhibited prebiotic effects on Lactobacillus casei , L. pentosus , L. plantarum , W. cibaria , B. animalis , and S. cerevisiae , which was different from this study result [ 17 ]. Several other studies have shown that each prebiotic oligosaccharide has its own prebiotic effect on specific probiotic strains [ 36 , 37 , 38 ]. The results of these studies indicate that the prebiotic effects of lactic acid strains vary depending on the type and structure of the oligosaccharides produced.…”
Section: Resultsmentioning
confidence: 99%
“…bassiana SAN01 Bgl was partially purified and concentrated via (NH 4 ) 2 SO 4 precipitation [31] and utilized in the hydrolysis of cellobiose. The 20 mL reaction mixture contained cellobiose at a final concentration of 1700 µg/mL and 50 U/mL of the B. bassiana Bgl in 0.1 mM sodium acetate buffer (pH 5.0) [32]. The reaction was performed for 24 h at 35 °C, samples were withdrawn at intervals, and the reaction was terminated by heating for 5 min at 100 °C in a boiling water bath.…”
Section: Hydrolysis Of Cellobiose By B Bassiana San01 β-Glucosidasementioning
confidence: 99%